2017
DOI: 10.1093/ejcts/ezx469
|View full text |Cite
|
Sign up to set email alerts
|

Multiple reoperations on the aortic valve: outcomes and implications for future potential valve-in-valve strategy†

Abstract: Multiple AV reoperations carry an acceptable risk of early postoperative mortality, particularly for isolated valve replacements of SVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Our mortality was in line with already published data, being between 7.3% and 10.9% [ 15 , 16 , 17 , 18 , 19 ]. Among predictors of mortality, our univariate analysis found that CPB time, aortic cross-clamping time, NYHA ≥ 3, urgency setting and endocarditis were significant predictive factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our mortality was in line with already published data, being between 7.3% and 10.9% [ 15 , 16 , 17 , 18 , 19 ]. Among predictors of mortality, our univariate analysis found that CPB time, aortic cross-clamping time, NYHA ≥ 3, urgency setting and endocarditis were significant predictive factors.…”
Section: Discussionsupporting
confidence: 93%
“…Of interest, replacement of mitral bioprosthesis was a risk factor for death, gastrointestinal and pulmonary complications. A similar result was reported by Jones et al and Lytle et al [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], whose studies demonstrated that patients undergoing mitral valve replacement have a higher risk of mortality than patients undergoing aortic valve replacement, mainly due to post-operative acute myocardial infarction, rupture of the left ventricle and arrhythmias. Nevertheless, the causes of death in our patients in group B were multi-organ failure and cardiogenic shock.…”
Section: Discussionsupporting
confidence: 87%
“…Postoperative early and late transition probabilities specific to mAVR ( Table E1 ) and the Ross procedure ( Table E2 ) were derived from published reports. 2 , 3 , 5 , 7 , 8 , 11 , 12 , 13 , 14 , 15 , 16 These transition probabilities reflected risks of developing various procedure-specific complications and reinterventions, in addition to the mortality associated with these adverse events.…”
Section: Methodsmentioning
confidence: 99%
“…This is also a single center's experience, making it less generalizable to other centers with lower-volume or different care team. Joshi et al E4 Description This is a single-center retrospective cohort study (2007-2016) that investigates the morbidity and mortality for patients (n = 316) who have had a 1 (n = 263), 2 (n = 42), and 3 (n = 11) redo AVRs. Strengths/applicability This is a large study that provides probabilities regarding the morbidity and mortality after a redo AVR; these are probabilities that are infrequently reported and difficult to find in published reports.…”
Section: Appendix E1mentioning
confidence: 99%
See 1 more Smart Citation